2014
DOI: 10.1007/s40806-014-0004-2
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Attractiveness Perception of Men’s Dance Movements in Relation to Self-Reported and Perceived Personality

Abstract: Recent research on women's ratings of men's dance movements indicates that women derive similar cues of male "quality" (e.g., physical strength) from movement as from faces and bodies. Whether this extends to personality assessment is yet unclear. We recorded dance movements of 80 men using 3D optical motion-capture technology and secured selfreports of men's personality standings. Dance movements were applied to a uniform, shape-standardized virtual humanoid character (avatar) and presented to women as 15-s v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“… Weege et al (in press a) showed that men’s self-reported (NEO-FFI) personality scores did not correlate with women’s ratings of men’s personality standings, i.e., women were not able to accurately assess men’s personality from dance movements—a result that corroborates research investigating relationships of self-reported personality with observer-reports of personality based on gait ( Thoresen et al, 2012 ). However, women’s ratings of a man’s dance attractiveness correlated negatively with their ratings of his neuroticism, and positively with their ratings of his conscientiousness.…”
Section: Cross-cultural Perception Of Body Movementsupporting
confidence: 62%
“… Weege et al (in press a) showed that men’s self-reported (NEO-FFI) personality scores did not correlate with women’s ratings of men’s personality standings, i.e., women were not able to accurately assess men’s personality from dance movements—a result that corroborates research investigating relationships of self-reported personality with observer-reports of personality based on gait ( Thoresen et al, 2012 ). However, women’s ratings of a man’s dance attractiveness correlated negatively with their ratings of his neuroticism, and positively with their ratings of his conscientiousness.…”
Section: Cross-cultural Perception Of Body Movementsupporting
confidence: 62%
“…If Schmitt and Atzwanger (1995) are correct, manipulating gait speed should have an effect on perception, with more positive assessments provided to fast walkers and less positive assessments provided to slow walkers. However, it is also plausible that faster movements are associated with less positive assessments, as has been reported for dance ( Weege et al, 2015a ), and that slow movements indicate self-composure and security, for example.…”
Section: Introductionmentioning
confidence: 85%
“…Gait recordings were obtained from 80 men, aged 18 to 42 years, recruited at Northumbria University (United Kingdom) as part of a large-scale study on body movement in relation to anthropometry and personality (for related reports, see Fink et al, 2012 , 2014 , 2016 ; Weege et al, 2012 , 2015a , b ; Hufschmidt et al, 2015 ). No participants reported any injuries that might influence natural movements.…”
Section: Methodsmentioning
confidence: 99%
“…Participants were 80 men, aged 18-42 years, recruited at Northumbria University (U.K.) as part of a large-scale study on body movement in relation to anthropometry and personality (for related reports see Fink et al, 2012;Fink, Weege, Neave, Ried, & do Lago, 2014;Hufschmidt et al, 2015;Weege, Lange, & Fink, 2012;Weege et al 2015a;Weege, Barges, Pham, Shackelford, & Fink, 2015b). Participants reported that they did not have injuries that might influence their natural movements.…”
Section: Strength and Gait Recordingsmentioning
confidence: 99%